1979
DOI: 10.1017/s002185960008607x
|View full text |Cite
|
Sign up to set email alerts
|

Use of water by six grass species. 1. Dry-matter yields and response to irrigation

Abstract: The yield and quality of herbage produced by six grasses (perennial ryegrass, cocksfoot, timothy, rough-stalked meadow grass, tall fescue and Italian ryegrass) were examined both without irrigation and under two irrigation regimes. Water was applied according to the potential soil water deficit (potential SWD): the soil was either partially returned to field capacity (FC) after each cut or fully returned to FC whenever the potential SWD reached 25 mm. The swards were cut either at 3 (C 3 ) or 6 (C 6 ) week int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…In this project, even in the absence of moisture stress, Island 2006 1 6621a 6048a 5116b 4639b 198 2 2723a 2603a 1851b 1798b 110 Total 9345a 8651a 6968b 6437b 265 2007 1 7637a 7243ab 7057ab 6432b 258 2 2663a 2204a 2347a 2552a 192 Total 10300a 9448ab 9404ab 8984b 262 Picture Butte 2006 1 5964a 6715b 6266ab 6652b 143 2 3404a 3872a 3700a 3942a timothy did not grow vigorously in hot summer temperatures. Others (Garwood et al 1979;Riley 1992) have reported similar observations on the effect of temperature on timothy growth. Timothy hay does not grow well in hot and dry, and hot or dry climatic conditions (Smith 1972;Garwood et al 1979;Riley 1992;Hutton 1994).…”
Section: Dry Matter Yieldmentioning
confidence: 59%
See 3 more Smart Citations
“…In this project, even in the absence of moisture stress, Island 2006 1 6621a 6048a 5116b 4639b 198 2 2723a 2603a 1851b 1798b 110 Total 9345a 8651a 6968b 6437b 265 2007 1 7637a 7243ab 7057ab 6432b 258 2 2663a 2204a 2347a 2552a 192 Total 10300a 9448ab 9404ab 8984b 262 Picture Butte 2006 1 5964a 6715b 6266ab 6652b 143 2 3404a 3872a 3700a 3942a timothy did not grow vigorously in hot summer temperatures. Others (Garwood et al 1979;Riley 1992) have reported similar observations on the effect of temperature on timothy growth. Timothy hay does not grow well in hot and dry, and hot or dry climatic conditions (Smith 1972;Garwood et al 1979;Riley 1992;Hutton 1994).…”
Section: Dry Matter Yieldmentioning
confidence: 59%
“…Others (Garwood et al 1979;Riley 1992) have reported similar observations on the effect of temperature on timothy growth. Timothy hay does not grow well in hot and dry, and hot or dry climatic conditions (Smith 1972;Garwood et al 1979;Riley 1992;Hutton 1994). Smith (1972) compared timothy growth under different temperatures and reported that it was more productive under a 21/168C day/night combination than under warmer (32/278C, 27/218C) or colder (16/108C) conditions.…”
Section: Dry Matter Yieldmentioning
confidence: 59%
See 2 more Smart Citations
“…Some studies have reported no effect of soil-moisture conditions on the digestibility of forages (Hidiroglou et al, 1966;Taylor et al, 1976;Spurway et al, 1976). Garwood et al (1979) …”
Section: Inconsistent Effectsmentioning
confidence: 99%